Combination of LFP‐TRIR spectroscopy and DFT computation as a tool to determine the intermediate during the photooxidation of triarylphosphine. (18th October 2014) - Yasui, Shinro; Badal, Md. Mizanur Rahman; Kobayashi, Shinjiro; Mishima, Masaaki
<x xml:space="preserve">Abstract</x> Laser flash photolysis‐time‐resolved infrared spectroscopy (LFP‐TRIR) was performed on an acetonitrile or dichloromethane solution of triarylphosphines, Ar3P, in air. A transient spectrum consisting of several absorption bands appeared in the region of 1050–1300 cm−1 on the TRIR on a microsecond timescale, which disappeared on a millisecond timescale. To identify the observed transient intermediate, the IR spectra of possible intermediates of the photoreaction were simulated by theoretical calculations based on density functional theory (DFT). The IR spectrum simulated for the phosphine peroxidic radical cation, Ar3P+OO, well predicted the observed IR spectrum, showing that Ar3P+OO is formed as a transient intermediate upon the LFP of Ar3P in air. Copyright © 2014 John Wiley & Sons, Ltd.